The Effect of Career Development on Employee Performance and Employee Commitment Among Employees at XYz. - ismail, fadillah (Research in Management of Technology and Business, 2022)
Career development in an organization is an important aspect and is seen as a way to retain the workforce. This study evaluated the effect of career development on work performance and work commitment among workers at XYz Company. This study emphasizes the elements of task performance, contextual performance, adaptive performance for employee performance. For work commitments, this study uses the elements affective, normative, active continuance, elements. The quantitative research approach along with cross-sectional research design is used to collect data from employees in XYz Company as target population through self-conducted and also online questionnaire, google form. The results of the current study provide empirical evidence on key issues related to workload, stress from lack of manpower and facilities. The results show a moderate level of performance and commitment of employees. Career development has a positive and significant relationship to employee performance and commitment with a value P = 0.000 for both variables namely p